2009
DOI: 10.1088/0964-1726/18/2/025011
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of parameters to achieve temperatures required to initiate the shape-memory effect of magnetic nanocomposites by inductive heating

Abstract: The activation of the shape-memory effect of nanocomposites (NC) by alternating magnetic fields requires exceeding the switching temperature T s. Different factors, which are influencing this process, have been investigated exemplarily. The intrinsic properties of magnetic nanoparticles (MNP), their content and distribution in the polymer matrix as well as the heat transport conditions, which are essentially determined by the surface to volume ratio (S/V) of the specimens and the surroundings, are influencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 28 publications
4
68
1
1
Order By: Relevance
“…In addition H required for indirect heating to T mid = T max > T m,PEG = 40°C and T high = T max > T m,PCL = 70°C were determined for CLEG(040)C05 to H mid = 22.2 kA·m -1 and H high = 29.4 kA·m -1 . The inserted model calculation based on Equation (4) showed that T max correlated with H 2 as previously reported for other composite systems [38,40]. Here it becomes apparent, that for CLEG(040)C02 the obtained data and the theoretical prediction of the model calculation were in good agreement, while CLEG(040)C05 and CLEG(040)C10 showed a significant deviation in the H-range of 15 kA·m -1 to H = 22.4 kA·m -1 , which might be related to the higher particle loading.…”
Section: Magnetic Heating Experimentssupporting
confidence: 80%
See 3 more Smart Citations
“…In addition H required for indirect heating to T mid = T max > T m,PEG = 40°C and T high = T max > T m,PCL = 70°C were determined for CLEG(040)C05 to H mid = 22.2 kA·m -1 and H high = 29.4 kA·m -1 . The inserted model calculation based on Equation (4) showed that T max correlated with H 2 as previously reported for other composite systems [38,40]. Here it becomes apparent, that for CLEG(040)C02 the obtained data and the theoretical prediction of the model calculation were in good agreement, while CLEG(040)C05 and CLEG(040)C10 showed a significant deviation in the H-range of 15 kA·m -1 to H = 22.4 kA·m -1 , which might be related to the higher particle loading.…”
Section: Magnetic Heating Experimentssupporting
confidence: 80%
“…For magnetic nanocomposites the specific absorption rate (SAR) or specific loss power is a key parameter, which is defined as the amount of heat released by a unit weight of the composite material per unit time [38,40]. It was further reported that SAR is proportional to the observed temperature difference "T = T max -'T env , which can be correlated to the square of the magnetic field strength (H 2 ) (Equation (4)), where k is a material related constant, which depends on several factors (e.g.…”
Section: Magnetic Heating Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose an alternating magnetic field is applied, causing strong particle motion inside the polymer matrix and thus local heating effects. Some recent advances and fundamental insights in this field were given by Lendlein's group [211,212]. Since magnetically induced actuation allows the triggering of the SM effect in a remote and wireless manner, the technique should be applicable to medical devices.…”
Section: Magnetosensitive Smp Compositesmentioning
confidence: 99%